Obtaining Bixin- and Tocotrienol-Rich Extracts from Peruvian Annatto Seeds Using Supercritical CO2 Extraction: Experimental and Economic Evaluation - (:unkn) unknown (MDPI, 2024)
Currently, Bixa orellana L. extracts are used as a color source in the food, pharmaceutical, and cosmetic industries because they are important as a potential source of antioxidant activity. The extraction is carried out by conventional methods, using al...
Keywords: Semillas de achiote; Extracción supercrítica